2019
DOI: 10.1017/s1049023x19005028
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Treatment with Continuous Positive Airway Pressure on Acute Carbon Monoxide Poisoning

Abstract: Introduction:Approximately 50,000 patients per year present at emergency departments (EDs) because of carbon monoxide (CO) intoxication. The hypothesis of this study was that the half-life of CO and the regression period of complaints could be reduced more rapidly by applying oxygen with the Continuous Positive Airway Pressure (CPAP) modality using a non-invasive mechanical ventilator.Methods:The patients were divided into Group 1 and Group 2 in terms of the treatment method applied. Patients in Group 1 receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
3
0
3
Order By: Relevance
“…Previous studies have also indicated that CPAP can be an effective treatment alternative to conventional oxygen therapy in patients with COP. [6][7][8] A clear limitation in this report is that the patient did not undergo an overnight PSG examination before COP to fully confirm that she did not have pre-existing OSA. However, her family denied that she had OSA symptoms before COP.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have also indicated that CPAP can be an effective treatment alternative to conventional oxygen therapy in patients with COP. [6][7][8] A clear limitation in this report is that the patient did not undergo an overnight PSG examination before COP to fully confirm that she did not have pre-existing OSA. However, her family denied that she had OSA symptoms before COP.…”
Section: Discussionmentioning
confidence: 94%
“…Kelompok terapi CPAP mengalami perbaikan keluhan nyeri kepala yang lebih baik dibandingkan kelompok NRM, namun untuk keluhan lain, seperti mual, pusing, dan lemas, tidak dijumpai perbedaan bermakna. 24 Ventilasi non-invasif metode CPAP dengan sungkup ketat dapat menjadi alternatif terapi keracunan CO karena tersedia cukup luas dibandingkan dengan ketersediaan fasilitas terapi HBO. Proses eliminasi CO dari tubuh bergantung pada fraksi oksigen yang dihirup dan kecepatan difusi CO melalui membran alveoli-kapiler dan kecepatan ekspirasi.…”
Section: Patofisiologi Infeksi Dengue Sekunderunclassified
“…Son yıllarda yapılan çalışmalarda sürekli pozitif basınçlı ventilasyon (CPAP) kullanımının, yüksek akışlı oksijen tedavisine kıyasla COHb düzeyini daha hızlı azalttığı gösterildi. Bu sayede CPAP tedavisi alan hastaların semptomlarında hızlı düzelme ve acil takip süresini kısalma sağladığı gösterilmiştir (9,10). HBO tedavisi hastaların 1,4 atmosfer ve üzeri basınçlarda hiperbarik bölmelerde %100 oksijen solutulması olarak tanımlanabilir.…”
Section: öZunclassified